1998
DOI: 10.1152/ajpcell.1998.275.4.c988
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-mediated PGE2expression in human colonic fibroblasts

Abstract: We investigated prostanoid biogenesis in human colonic fibroblasts (CCD-18Co and 5 primary fibroblast cultures) and epithelial cell lines (NCM460, T84, HT-29, and LS 174T) and the effect of PGE2 on fibroblast morphology. Cytokine-stimulated PGE2production was measured. PGH synthase-1 and -2 (PGHS-1 and -2) protein and mRNA expression were evaluated. Basal PGE2 levels were low in all cell types (0.15–6.47 ng/mg protein). Treatment for 24 h with interleukin-1β (IL-1β; 10 ng/ml) or tumor necrosis factor-α (50 ng/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
39
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 29 publications
5
39
0
Order By: Relevance
“…PGE 2 production was increased in colonic fibroblasts and in IBD patients. Intestinal fibroblasts, in addition to epithelial cells, could be targets for PGE 2 and sites of colonic prostanoid biosynthesis in vivo (Kim et al, 1998). The expression of COX-2 has also been observed after Salmonella infection in intestinal epithelial cells (Singer et al, 1998), and COX-2 protein was reported to be expressed in three of eight colon cancer cell lines, including HT29 (Parker et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PGE 2 production was increased in colonic fibroblasts and in IBD patients. Intestinal fibroblasts, in addition to epithelial cells, could be targets for PGE 2 and sites of colonic prostanoid biosynthesis in vivo (Kim et al, 1998). The expression of COX-2 has also been observed after Salmonella infection in intestinal epithelial cells (Singer et al, 1998), and COX-2 protein was reported to be expressed in three of eight colon cancer cell lines, including HT29 (Parker et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 and other prostanoids are generated through two bifunctional enzymes, cyclooxygenases (COXs)-1 and -2 (Kim et al, 1998). In general, COX-1 is constitutively expressed in a wide range of tissues, including the gastrointestinal tract and plays a role in the tissue homeostasis, e.g., maintenance of gastrointestinal integrity (Singer et al, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…49 Traditionally, the causation of colonic cancers was attributed largely 50 to genetic alterations within the epithelial compartment [10]. However, 51 recent evidence suggests that the stromal compartment also plays a 52 major role in COX-2-mediated carcinogenesis [11,[11][12][13][14][15][16][17][18][19][20][21]. 53 The stroma of an organ is underlying the epithelium, serving as 54 the connective tissue framework.…”
mentioning
confidence: 99%
“…Other 58 types of cells such as macrophages might also promote the tumorigenic 59 progression of intestinal epithelial cells by the activation of COX-2 sig-60 naling [23]. We have shown that colonic fibroblasts are a potent source 61 of inducible COX-2 and PGE 2 and that inflammatory factors such as 62 IL1-β, TNF-α and deoxycholic acid promote a sustained COX-2 expres-63 sion and PGE 2 production in colonic fibroblasts [12][13][14][15][16][17][18]. Maximal levels 64 of COX-2 expression and PGE 2 production were far greater in CAFs initi-65 ated from biopsies of colonic cancers than those in normal fibroblasts 66 (NFs) initiated from normal colorectums [13].…”
mentioning
confidence: 99%